Rural poverty and inequality in Ethiopia: does access to small-scale irrigation make a difference? - Namara, Regassa E.; Makombe, Godswill; Hagos, Fitsum; Awulachew, Seleshi Bekele (2008)
Ethiopia is an agrarian society in a land of drought and floods. Agricultural production, which is the source of livelihood for eight out of ten Ethiopians, is extremely vulnerable to climatic conditions. The causes of rural poverty are many including wide fluctuations in agricultural production as a result of drought, ineffective and inefficient agricultural marketing system, under developed transport and communication networks, underdeveloped production technologies, limited access of rural households to support services, environmental degradation and lack of participation by rural poor people in decisions that affect their livelihoods. However, the persistent fluctuation in the amount and distribution of rainfall is considered as a major factor in rural poverty. Cognizant of this reality the successive Ethiopian governments and farmers have made investments in small scale irrigation schemes. This paper aims to assess the efficacy of these investments in reducing poverty based on data obtained from a survey of 1024 farmers drawn from four major regional states of Ethiopia. The Foster, Greer and Thorbecke poverty measures were used to compare the incidence, depth and severity of poverty among groups of farmers defined by relevant policy variables including access to irrigation. In order to explore the correlates of rural poverty and their quantitative significance, logistic regression model was estimated. The main conclusion of the study is that the incidence, depth and severity of poverty is affected more by the intensity of irrigation use (as measured by the size of irrigated area) than mere access to irrigation. Alternatively, there seems to be an economy of scale in the poverty irrigation relationship.